Battery energy scheduling and benefit distribution models under shared energy storage: A mini review - Kong, Shaohua; Wang, Yuchen; Xie, Dongwei (Frontiers in Energy Research, 2023)
Energy storage solutions are strategically important for achieving carbon neutrality and carbon peaking goals. However, high installation costs, demand mismatch, and low equipment utilization have prevented the large-scale commercialization of traditional energy storage. The shared energy storage mode that relies on sharing economy can effectively overcome these problems and has recently attracted widespread attention. In this mini-review, firstly, the concept of shared energy storage is discussed and its application in different countries is illustrated. Second, two core issues in the shared energy storage research--optimal energy scheduling and rational profit distribution— are sorted out and the common modeling approaches and solving algorithms are summarized. Additionally, the dilemma of balancing energy efficiency with distribution fairness faced by the practical application of shared energy storage is pointed out. On this basis, blockchain technology is pointed out to solve the above dilemma of shared energy storage and key directions are given for future research.